Impact of cold ischemia time on the outcomes of kidneys with Kidney Donor Profile Index ≥85%: mate kidney analysis ‐ a retrospective study. (23rd February 2018) - Sampaio, Marcelo S.; Chopra, Bhavna; Tang, Amy; Sureshkumar, Kalathil K.
Summary: The new kidney allocation system recommends local and regional sharing of deceased donor kidneys (DDK) with 86–100% Kidney Donor Profile Index (KDPI) to minimize discard. Regional sharing can increase cold ischemia time (CIT) which may negatively impact transplant outcomes. Using a same donor mate kidney model, we aimed to define a CIT that should be targeted to optimize outcomes. Using Organ Procurement and Transplant Network/United Network for Organ Sharing database, we identified recipients of DDK from 2000 to 2013 with ≥85% KDPI. From this cohort, three groups of mate kidney recipients were identified based on CIT: group 1 (≥24 vs. ≥12 to <24 h), group 2 (≥24 vs. <12 h), and group 3 (≥12 to <24 vs. <12 h). Adjusted delayed graft function (DGF), and graft and patient survivals were compared for mate kidneys. DGF risk was significantly lower for patients with CIT <12 vs. ≥24 h in group 2 (adjusted OR: 0.25, 95% CI: 0.12–0.57, P < 0.001) while trending lower for CIT ≥12 to <24 vs. ≥24 h in group 1 (adjusted OR: 0.78, 95% CI: 0.59–1.03, P = 0.08) and CIT <12 vs. ≥12 to <24 h in group 3 (adjusted OR: 0.74, 95% CI: 0.55–1.0, P = 0.05). Adjusted graft and patient survivals were similar between mate kidneys in all groups. Minimizing CIT improves outcomes with regional sharing of marginal kidneys.